2005
DOI: 10.1074/jbc.m500711200
|View full text |Cite
|
Sign up to set email alerts
|

REL1, a Homologue of Drosophila Dorsal, Regulates Toll Antifungal Immune Pathway in the Female Mosquito Aedes aegypti

Abstract: Signaling by

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
120
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(124 citation statements)
references
References 40 publications
(49 reference statements)
3
120
0
1
Order By: Relevance
“…However, recent studies have shown that the Aedes orthologue of REL1 is not involved in defense against bacteria but only against fungal infections (32). Likewise, our preliminary results in Anopheles indicate that REL2 is the only NF-B factor implicated in the antibacterial defense against E. coli and S. aureus.…”
Section: Discussionsupporting
confidence: 50%
“…However, recent studies have shown that the Aedes orthologue of REL1 is not involved in defense against bacteria but only against fungal infections (32). Likewise, our preliminary results in Anopheles indicate that REL2 is the only NF-B factor implicated in the antibacterial defense against E. coli and S. aureus.…”
Section: Discussionsupporting
confidence: 50%
“…The other is that BmRelish1 has a higher ability to enhance the promoter activity of AMP genes than BmRels. Dorsal and Relish homologs have also been found in other insects, such as Anopheles gambiae, 36,37) Aedes aegypti, 38,39) and Tribolium castaneum, 40) but differences in the amounts of Rel family proteins have not yet been reported in other insects. Whether this phenomenon is silkworm-or Lepidoptera-specific ought to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…signal (NLS) (RKRQK) which characterize all NF-B family of proteins. Interestingly, the TD of CrNF B lacks the polyglutamine, polyalanine, and polyasparagine stretches, which characterizes the TD of several insect Dorsal-like proteins (12). A phylogenetic analysis shows that CrNF B clustered among Dorsal-like proteins that belong to the invertebrate class II NF-B (Fig.…”
mentioning
confidence: 99%